Analisa Faktor-Faktor Makroekonomi Terhadap Kinerja Investasi Saham Periode 2010 – 2012 - Erric Wijaya (STIE Indonesia Banking School, 2015)
This study discusses the macroeconomic effect on the performance of mutual fund shares. Macroeconomic variables used are economic growth, inflation, bank interest rates, and exchange rates, while the performance of mutual fund shares calculated using the Sharpe ratio. This study uses the data in the form of panel data with quarterly time series ranging between 2010-2012. The equation used is multiple regression equation Ordinary Least Square (OLS). After performing the classical assumption, and normality of the data, the results of the study showed that partially there are significant macroeconomic variables consist of exchange rate, inflation, and economic growth that influence the performance of mutual fund shares quarterly in period 2010-2012. While the bank's interest rate variable has no significant effect on the performance of mutual fund shares. However, the macroeconomic variables affect the performance of mutual fund shares simultaneously. Therefore the ultimate findings of this study is that macroeconomic variables only affect the performance of mutual funds in the amount of 35.3%, while the remaining 64.7% is influenced by other factors, especially the internal factors of mutual fund shares